2015
DOI: 10.1002/ar.23169
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Anatomy of the Cranial Cervical Ganglion in the Dromedary Camel (Camelus dromedarius)

Abstract: The detailed morphology and topography of the cranial cervical ganglion (CCG) with its surrounding structures were studied in 10 sides of five heads of adult one-humped camel to determine its general arrangement as well as its differences and similarities to other animals. The following detailed descriptions were obtained: (1) the bilateral CCG was constantly present caudal to cranial base at the rostroventral border of the occipital condyle over the caudolateral part of nasopharynx; (2) the CCG was always in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 18 publications
6
14
0
Order By: Relevance
“…In this study, bilateral CCG was constantly noted in all specimens which is concordant with findings of all reported anatomical studies in the adults and fetuses of animals and humans (Hara et al, ; Pospieszny and Bruzewicz, ; Kawashima, ; Kawashima and Sato, ; Nourinezhad et al, ).…”
Section: Caudal Cervical Ganglionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, bilateral CCG was constantly noted in all specimens which is concordant with findings of all reported anatomical studies in the adults and fetuses of animals and humans (Hara et al, ; Pospieszny and Bruzewicz, ; Kawashima, ; Kawashima and Sato, ; Nourinezhad et al, ).…”
Section: Caudal Cervical Ganglionsupporting
confidence: 92%
“…According to them, in the youngest fetuses the CCG was constantly located near the base of the skull, whereas in the older fetuses the CCG tended to be slightly more caudally at the level of the CV1, which is found in the adult pig (Kabak et al, ). In this study, such a positional decent of the CCG was not observed and the CCG was located slightly caudal to the cranial base, almost similar to that noted in the 2–3 months old lambs (Appleton and Waites, ) and dromedary camels and bovines (Nourinezhad et al, ). These reasons may be recognized as the skeletotopical differences between the fetal sheep and fetal humans; nevertheless, it remains unclear why the CCG in the fetal pig tends to be positioned slightly caudal.…”
Section: Caudal Cervical Ganglionsupporting
confidence: 88%
See 3 more Smart Citations